Reduced Language Lateralization in Autism and the Broader Autism Phenotype as Assessed with Robust Individual‐Subjects Analyses. Issue 10 (15th September 2020) - Jouravlev, Olessia; Kell, Alexander J.E.; Mineroff, Zachary; Haskins, Amanda J.; Ayyash, Dima; Kanwisher, Nancy; Fedorenko, Evelina
Abstract : One of the few replicated functional brain differences between individuals with autism spectrum disorders (ASD) and neurotypical (NT) controls is reduced language lateralization. However, most prior reports relied on comparisons of group‐level activation maps or functional markers that had not been validated at the individual‐subject level, and/or used tasks that do not isolate language processing from other cognitive processes, complicating interpretation. Furthermore, few prior studies have examined functional responses in other brain networks, as needed to determine the spatial selectivity of the effect. Using functional magnetic resonance imaging (fMRI), we compared language lateralization between 28 adult ASD participants and carefully pairwise‐matched controls, with the language regions defined individually using a well‐validated language "localizer" task. Across two language comprehension paradigms, ASD participants showed less lateralized responses due to stronger right hemisphere activity. Furthermore, this effect did not stem from a ubiquitous reduction in lateralization of function across the brain: ASD participants did not differ from controls in the lateralization of two other large‐scale networks—the Theory of Mind network and the Multiple Demand network. Finally, in an exploratory study, we tested whether reduced language lateralization may also be present in NT individuals with high autism‐like traits. Indeed, autistic trait load in a large set of NT participants ( n = 189) was associated with less lateralized language responses. These results suggest that reduced language lateralization is robustly associated with autism and, to some extent, with autism‐like traits in the general population, and this lateralization reduction appears to be restricted to the language system. Lay Summary: How do brains of individuals with autism spectrum disorders (ASD) differ from those of neurotypical (NT) controls? One of the most consistently reported differences is the reduction of lateralization during language processing in individuals with ASD. However, most prior studies have used methods that made this finding difficult to interpret, and perhaps even artifactual. Using robust individual‐level markers of lateralization, we found that indeed, ASD individuals show reduced lateralization for language due to stronger right‐hemisphere activity. We further show that this reduction is not due to a general reduction of lateralization of function across the brain. Finally, we show that greater autistic trait load is associated with less lateralized language responses in the NT population. These results suggest that reduced language lateralization is robustly associated with autism and, to some extent, with autism‐like traits in the general population. Autism Res 2020, 13: 1746–1761. © 2020 International Society for Autism Research and Wiley Periodicals LLC